HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG DISMENORE DENGAN UPAYA PENANGANAN DISMENORE - Safitri M; Wangi G; Rahmawati N (Universitas Harapan Bangsa Purwokerto, 2013)
Dysmenorrhea or menstrual pain is a symptom that often leads young woman wentto the doctor for consultation and treatment. Seeing the impact of dysmenorrhea is said thatdysmenorrhea is one of the problems in the lives of young women, forcing them to use avariety of ways to deal with the pain of dysmenorrhea. Preliminary studies conducted by theauthor in December 2011 in two SMA Banyumas namely MAN MAN 1 and 2 Purwokertoshowed that the incidence of dysmenorrhea in MAN 1 Purwokerto higher (40) than theincidence of dysmenorrhea in MAN 2 Purwokerto (20). Determine the relationship of young women knowledge about dysmenorrheadysmenorrhea response efforts in MAN 1 Purwokerto in 2012Methods: This study was descriptive correlation with cross sectional approach. The sampleused was cluster random sampling, the population in this study were all teenage girls in classX and a sample of 38 respondents. The instrument used was a questionnaire with dataanalysis using chi-square. From the results, most of it is pretty much as 17 respondents (44.7%), most of it ishandled as many as 25 respondents (65.8%), there is a correlation between the knowledge ofthe young women with dysmenorrhea dysmenorrhea treatment efforts in MAN 1 Purwokertoin 2012 with a value of count x2> x2 table (9.347> 5.991). There is a relationship between knowledge about young women with dysmenorrheadysmenorrhea treatment efforts in MAN 1 Purwokerto in 2012. Keywords: Dysmenorrhea, Young Women, Knowledge